Oral hygiene level and prevalence of gingivitis amongst pregnant women in a nigerian teaching hospital - Mohammad A. Kaura; Halima M. Bawa; Edugie Ekuase; Babatunde O. Bamgbose (DiscoverSys Inc., 2021)
Objective: The aim of this study was to assess the prevalence of gingivitis among pregnant women attending ante-natal clinic in Aminu Kano Teaching Hospital (AKTH) KanoMaterial and Methods: This was a cross-sectional study involving pregnant women attending antenatal clinic at AKTH. A convenience sampling technique was used to recruit consenting pregnant women who were continuously enrolled until the calculated sample size was reached. A structured, interviewer-administered questionnaire was used to obtain the socio-demographic and other relevant data. An intraoral examination was performed by the researcher to assess their oral and gingival health status. Results: A total of 350 respondents out of the 376 approached participated in the study giving a response rate of 93.1%. A prevalence rate of gingivitis recorded was 82.3%.Conclusion: Gingivitis is highly prevalent among the pregnant women studied with no significant association between oral hygiene aids used and oral hygiene status. However, there was significant association between oral hygiene status and gingival status.